Analisis Penerapaan Prinsip 5C Pada Peyaluran Pembiayaan Murabahah Dalam Menurunkan Tingkat Pembiayaan Macet : Studi Kasus Pada Bank SUMUT Cabang Pembantu Syariah Lubuk Pakam - Nurainun Putri; Yenni Samri Juliati Nasution; Muhammad Lathief Ilhamy Nasution (STIKes Ibnu Sina Ajibarang, 2023)
The purpose of this study was to determine the supporting and inhibiting factors in Murabahah financing at Bank Sumut Syariah Sub-Branch Lubuk Pakam and the results of the analysis of the application of the 5C principle in Murabahah financing at Bank Sumut Syariah Sub-Branch Lubuk Pakam. This research method uses descriptive qualitative research. While the data is done using observation, documentation and interview techniques. The data analysis model used in this research is qualitative analysis of the Miles and Huberman model, namely by reducing data, presenting data and drawing conclusions. The results in this study indicate that: Internal obstacles faced by Bank SUMUT Lubuk Pakam Syariah Sub-Branch in applying the 5C Principle, namely; limited customer information, limited technology, product suitability, property valuation, supervision and control, economic and industrial conditions. And external constraints faced by Bank SUMUT Lubuk Pakam Syariah Sub-Branch in applying the 5C Principle, namely; macroeconomics, changes in government policy, public consumption patterns, political uncertainty, regulatory changes.